The bottom line: an ethnography of for-profit elderly residential care - Greener, Joe (2011)
In the last 20 years the UK’s elderly residential care system has become progressively more privatised with an increase in the number of for-profit organisations delivering these services. This study is a participant observation of care work in one privatised elderly residential care home (‘Meadowvale’), owned and operated by a large provider of such services (‘Moonlight Care’). It provides a rich ethnographic depiction of life at Meadowvale both from the point of view of the workers and the residents. The thesis frames these ethnographic findings against pro-privatisation discourses which argue that serious raises in standards of service delivery are to be made from instilling profit motives within social care systems.